Training exercise on complaints work-related musculoskeletal disorders (WMSDs) in the administration employees of BPOM lampung - Tania, Chika (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
According to World Health Organization data, the musculoskeletal incidence is estimated to reach 60% of all occupational diseases. Steps that can be taken to overcome musculoskeletal complaints include stretching exercises that can flex or relax, increase elasticity, and gain comfort in the muscles. This study used the quasi-experimental method with a pre and post-test control group design approach. This study used 50 samples divided into two groups, namely 25 respondents for the control group who were not given stretching exercises and 25 respondents for the treatment group who were given stretching exercises for 14 working days. In each group, a musculoskeletal complaint was assessed before and after treatment. Data were tested by the Chi-Square test to determine the differences in each group and the effect of stretching exercises on musculoskeletal complaints. The initial assessment of musculoskeletal complaints before stretching exercises in the treatment group was found to be mostly with moderate complaints, and in the control group, the majority were with moderate complaints. Data analysis with statistical tests showed that there were differences in musculoskeletal complaints in the treatment group with a value of p = 0.030. There is the influence of stretching exercises on complaints of work-related musculoskeletal disorders (WMSDs) in the administrative staff of BPOM Lampung.